Kinetics on roasting reduction of limonitic laterite ore using coconut-charcoal and anthracite reductants. (1st March 2019) - Petrus, Himawan Tri Bayu Murti; Putera, Andreas Diga Pratama; Sugiarto, Edi; Perdana, Indra; Warmada, I Wayan; Nurjaman, Fajar; Astuti, Widi; Mursito, Anggoro Tri
Highlights: Bioreductor could be a sustainable reductor in the nickel processing. Coconut charcoal has reduction performance similar to anthracite. Direct reaction mechanism controls the reduction of nickel. Abstract: In recent years, the demand for processing nickel laterite ore, which accounts for about 72% of the world nickel resources, increases as the continuous depletion of sulphidic nickel ore. With as many as 60% of nickel, usage goes into stainless steel production combined with the high price of its pure form, nickel pig iron (NPI) has emerged into account from lateritic ores. However, until now, the process requires the use of coking coal which emits a huge amount of carbon dioxide during the reduction stage so that an initial study about using more environmentally-friendly carbon-based reductant to reduce carbon dioxide emission is deemed important. Limonitic laterite ore, coconut charcoal, and anthracite coal were used in the process. All materials were crushed to certain particular size and then mixed to form laterite-reductant pellets. In a muffle furnace, the pellets were roasted at a temperature of 800 °C, 900 °C, and 1000 °C. Initial analysis of laterite ore and reductant (both charcoal and anthracite) was conducted using X-ray fluorescence (XRF) and proximate analysis. X-Ray Diffraction (XRD) of the samples and the mass loss calculation, before and after the reduction process, were assessed to study the phase transformation and kinetic mechanism. To confirm the minerals in the limonitic laterite ore Thermogravimetric-differential thermal analysis (TG-DTA) was conducted. It is found that the dominating mineral in the limonitic laterite ore is goethite and a little portion of serpentine. The results indicated that hematite and magnetite were present in the roasted sample. From the data fitting, diffusion models match the trend properly and thus, indicated that direct reactions occur. Both Jander and Ginstling-Brounshtein model fit the data properly although Jander model gives the smallest error with the average least square fittings of 0.9778 and 0.9108 for laterite-anthracite and laterite-coconut crust charcoal sample, respectively. The related activation energy values obtained were 3.7092e + 04 and 4.4370e + 04 J/mol showing that coconut charcoal performs comparably as anthracite coal in the reduction of limonitic laterite ore.